Flexural strength of weathered granites: Influence of freeze and thaw cycles. (15th December 2017) - Noor-E-Khuda, Sarkar; Albermani, Faris; Veidt, Martin
Highlights: Non-destructive testing of Australian Granite's. Effect of freeze-thaw cycles on the flexural strength of granite. Ultrasonic pulse velocity of unweathered and weathered granite. Correlation between flexural strength and UPV. Abstract: The effect of freeze-thaw cycles (FTC) on the flexural strength of granite panels is investigated in this paper. Specimens from three different types of Australian granite were sampled. Fifteen specimens were used as control (unweathered) specimens while another 36 specimens were subjected to accelerated weathering consisting of 100 FTC over a period of 34 days. A controlled freeze-thaw chamber and a temperature range between −10 °C and +70 °C was used for this purpose. Ultrasonic pulse velocity (UPV) of the specimens was measured before and after FTC testing. Flexural strength tests were conducted after the FTC were completed. Results showed that thin granite veneers suffered physical degradation accompanied by a noticeable reduction in UPV, density and flexural strength following FTC. Correlation between flexural strength and UPV and between unweathered and weathered UPV is proposed for the three types of Australian granite used in this paper.